Correction: WS2 quantum dots harvesting via sonication assisted liquid exfoliation for the electrochemical sensing of xanthine. (23rd March 2023) - Sakthivel, Arunkumar; Chandrasekaran, Anitha; Soosaimanickam, Charlin; Li, Chen-Zhong; Alwarappan, Subbiah
Abstract : Correction for 'WS2 quantum dots harvesting via sonication assisted liquid exfoliation for the electrochemical sensing of xanthine' by Arunkumar Sakthivel et al., New J. Chem., 2022, 46, 17066–17072, ; https://doi.org/10.1039/D2NJ03446H .